Clinical Usefulness of Linked Color Imaging for Detection and Characterization of UndifferentiatedType Early Gastric Cancer - In Kyung Yoo; Hyuk Lee; Young Il Kim; Joo Young Cho; Wan Sik Lee (Turkish Journal of Gastroenterology, 2023)
Background: Linked color imaging is based on the bioluminescent imaging technique, which enhances differences in mucosal color allowing for contrast-based detection of lesions. There have been reports which have investigated the usefulness of linked color imaging for assessing color values in endoscopy for early gastric cancer cases. However, these primarily focused on differentiated early gastric cancer. This study aimed to assess the efficacy of linked color imaging in analyzing the color differences between cancerous and noncancerous areas in undifferentiated-type early gastric cancer patients compared with conventional white light imaging. Methods: Forty-six patients were prospectively enrolled with undifferentiated-type early gastric cancer from 3 academic hospitals. All lesions were observed first by white light imaging followed by linked color imaging. An additional biopsy was taken from the surrounding mucosa to check for intestinal metaplasia, and test for Helicobacter pylori was performed. Color difference was measured in accordance with the International Commission on Illumination details. Results: The color difference value with linked color imaging was significantly higher, being more than twice that of white light imaging (26.82 ± 14.18 and 12.60 ± 6.42, P < .001), and this difference appeared to be similar in cases of accompanying Helicobacter pylori infection or intestinal metaplasia. In the subgroup analysis, color difference of poorly differentiated adenocarcinoma was notable in linked color imaging compared to white light imaging. Conversely, no statistically significant finding was present in signet ring cell carcinoma or mixed-type histology. Conclusion: Linked color imaging provides a significantly greater color difference between cancerous lesions and background noncancerous mucosa in undifferentiated-type early gastric cancer. Moreover, linked color imaging may differentiate between pathologic subgroups of undifferentiated-type early gastric cancer possibly due to characteristic cellular growth pattern. Cite this article as: Kyung Yoo I, Lee H, Il Kim Y, Young Cho J, Sik Lee W. Clinical usefulness of linked color imaging for detection and characterization of undifferentiated-type early gastric cancer. Turk J Gastroenterol. 2023;34(4):356-363.